The Mortgage Right as MurÄbaá¸¥ah Financing Security - Reni Anggriani; Galang Rizki; Wida Febriansyah (Jurnal Hukum Novelty, 2019)
Introduction to The Problem: In order to guarantee the legal certainty for the Islamic banking customer in murÄbaá¸¥ah financing is the requirement of mortgage right. The bank customer may use mortgage right as collateral in murÄbaá¸¥ah financing. Furthermore, the right can be implemented in the indebtedness, which is different from debt.Purpose/Objective Study: This research aims to find out the contract (al-â€˜aqd) that is used by the shariah bank to implement the mortgage rights in murÄbaá¸¥ah financing.Design/Methodology/Approach: This study is normative juridical research with emphasis beginning on a legal event and then looking for references to a norm system. Therefore, this legal research is conducted by examining primary and secondary legal materials, and non-legal materials relating to the application of Mortgage Rights in Financing, especially for murÄbaá¸¥ah financing. In this study, the approach was the statute approach by examining all laws and regulations relating to legal issues, and case approach by examining several cases that have a relationship with the legal issues to be discussed.Findings: The result of this study is that the implementation of mortgage right in murÄbaá¸¥ah financing is the possibility of using another contract made by sharia banking with its customers; the contract of acknowledgment of debt. This basis is used as the justification of the implementation of mortgage rights in murÄbaá¸¥ah financing.